Single Posthepatic Portosystemic Shunt Communicated With Internal Thoracic Vein and Azygos Continuation of the Caudal Vena Cava in a Dog - Ryo Takeuchi; Kumiko Ishigaki; Orie Yoshida; Tatsuya Heishima; Kaito Iida; Kazushi Asano (Veterinary Medicine and Science)
ABSTRACT Computed tomography angiography (CTA) was performed under general anaesthesia on a 7‐month‐old toy poodle that was referred with the chief complaints of salivation and neurological symptoms. The CTA revealed a rare form of posthepatic portosystemic shunt (PSS) via the suspected persistent left umbilical vein communicating with the internal thoracic vein in addition to an azygos continuation of the caudal vena cava (CVC). The patient underwent surgery for partial ligation of PSS on Day 4 after the initial examination. On Day 71, after the initial examination, a second surgery was performed for complete ligation. Approximately 10 years have passed since the patient's second surgery, and he is still healthy, and generally in good condition. Although the morphology of the shunt in this case was unusual and was accompanied by an azygos continuation of the CVC, a favourable course of treatment was obtained by ligating the shunt vessel. This case report suggests that CTA can reveal the complex morphological characteristics like our case. Surgical treatment in this case resulted in favourable progress, similar to that in dogs with commonly observed extrahepatic PSS.